Red-Ox Energetics and Holes Trapping in Yttrium-Substituted Barium Zirconate BaZr0.9Y0.1O2.95. Issue 4 (23rd February 2019) - Tsvetkov, Dmitry S.; Ivanov, Ivan L.; Malyshkin, Dmitry A.; Sereda, Vladimir V.; Yu. Zuev, Andrey
Abstract : The red-ox behavior and the nature of the hole conduction in BaZr0.9 Y0.1 O3-δ (BZY10) were studied by the set of complementary techniques including the measurements of the total conductivity, the Seebeck coefficient and the equilibrium oxygen partial pressure. As a result, the oxidation enthalpy of BZY10 was determined to be equal to −0.43 eV. It was concluded that holes present in BZY10 are of a small-polaron type with the migration enthalpy estimated as 0.06 eV. These holes also exhibit significant trapping by the acceptor ions. The dissociation energy of trapped holes was found to be equal to 0.95 eV. The similarities in the behavior of protons and holes in BZY10 were discussed.